Lifestyle Commodification: A Netnographic Analysis of the Digital Matcha Subculture on Instagram and TikTok - Ghaisani Farahiyah; Lady Yusticia Oceanie; Miftahul Nurul Janah (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The trend of matcha consumption has grown not only as a culinary preference but also as a significant component of social media popular culture. This study uses reflective-projective and subculture theories to examine how matcha is portrayed as a lifestyle symbol and consumption trend. Leovinger's reflective-projective theory describes how social media portrays aspirational images of health, beauty, and social standing while reflecting the reality of matcha drinking culture. Subculture theory is used to understand how digital communities create collective identities based on symbols associated with matcha. By observing content on the Instagram and TikTok platforms and applying thematic analysis, a qualitative ethnography technique is employed. The findings demonstrate that matcha is marketed not only as a beverage but also as a symbol of a particular socioeconomic class, a healthy lifestyle, and an aesthetic consumption trend. In addition to establishing a trend-based digital subculture, matcha is portrayed on social media as a representation of self-balance, modernity, and cultural connectivity. As a result, matcha culture transcends the culinary realm and becomes a social phenomena that serves as a means of constructing one's identity and a symbolic representation of consumption in the digital sphere.